Resiliensi dan motivasi diri: Life history tentang dewi, anak broken home sarat prestasi: Resilience and self-motivation: Life history of dewi, a child of broken home full of achievements - Regina Agistira Helena; Nanang Martono; Tri Rini Widyastuti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
This article tells the journey of a broken home child from a different side, namely from Dewi's success in education, while this point of view has not been studied by previous research. This research uses qualitative life history method. Data collection methods are in-depth interviews, observation, and documentation. This research was analyzed using the interactive analysis method. There are four important points in interactive analysis, namely data collection, data reduction, data presentation, and conclusion drawing. The results of this study found that Dewi as a broken home child has experienced resilience from the bad circumstances she faced. There are several things that make Dewi able to face these conditions, including the desire to rise from within and the awareness that she must study hard. The results of this study also found that there are several motivations for Dewi to rise and achieve, namely the desire to raise the status of her family, the desire to fight stereotypes about broken home children, and the desire to have a harmonious family in the future.